Solvent-free process for the synthesis of highly stretchable piezoresistive sensors based on polydimethylsiloxane filled with graphene nanoplatelets and carbon nanotubes. Issue 1 (January 2021) - Piscitelli, F.; Lo Gatto, M. L.; Rollo, G.; Filippone, G.; Lavorgna, M.
Abstract: This work reports on the design, the development, and a preliminary characterization of highly stretchable polydimethylsiloxane (PDMS) elastomers as matrices for piezoresistive composites with graphene nanoplatelets (GNPs) and carbon nanotubes (CNTs) applicable to aircrafts with morphing shape changes. The strategy adopted for the formulation of the polymeric matrices was to use precursors at low molecular weights, in order to avoid the use of solvents, and functionalized with lateral phenyl groups, to improve the filler dispersion and the filler-polymer interactions. The nanocomposites show high deformability (90%), high conductivity (0.85-0.9S/m), and piezoresistive behavior (Gauge Factor equal to 0.75). Additionally, CNT and GNP show a synergistic effect in the electrical conductivity, since the percolative threshold of hybrid nanocomposites is lower than those observed with CNT or GNP separately.